THE STUDENT’S SPEAKING ANXIETY AT GRADE IX IN SMP N 1 SIBOLGA - happy sri rezeki purba; Anni Zuraidah; Khairunnisah Khairunnisah (Linguistik : Jurnal Bahasa dan Sastra, 2021)
The purpose of this study was (1) to determine the factors of student’s speaking anxiety at grade IX of SMP N1 Sibolga  and (2 )how is the strategy of student’s at grade IX of SMP N1 Sibolga to minimize it  This study uses a qualitative research method with a case study approach. Then, the data collection was carried out through observation and interviews. Based on the research results, the factors that caused the student’s anxiety were communication anxiety, golden test, negative judgment, and teacher personality attitude, then the strategies used by the student were relaxation, positive thinking, peer search, preparation and non-verbal communication. Through this research, it is hoped that the student can decrease their anxiety by following strategies and it will be helpful to enhance their speaking ability